EFFECTIVENESS OF PEER COUNSELING EDUCATION USING THE HEALTH BELIEF MODEL APPROACH TO THE SUCCESS OF EXCLUSIVE BREASTFEEDING - Siregar, Ronni Naudur; Br. Brahmana, Nettietalia; Aritonang, Juneris (Jurnal Ilmiah Keperawatan, 2024)
Exclusive breastfeeding for babies aged 0-6 months is very beneficial both for the baby as immunity and for the mother to prevent breast cancer and other diseases. Existing data shows that there is still a low number of mothers who provide exclusive breastfeeding, around 48% of babies aged < 6 months do not receive exclusive breastfeeding. Urgency of Research, low coverage of the success of exclusive breastfeeding both at the national level, 65%, provincial and at the research location; the majority of mothers lack knowledge in efforts to successfully provide exclusive breastfeeding; It is still felt that the methods and media used in exclusive breastfeeding education are very monotonous and require holistic and continuous education. Peer education takes the form of in-depth sharing with peers as informants so that mothers absorb information well. Peer education can increase BSE and mother's motivation in breastfeeding. This type of research is quasi-experimental with a pre-post non-control group approach. The aim of this research is to analyze the effectiveness of peer education using the health belief model approach on the success of exclusive breastfeeding. The location of this research is Cinta Damai Village, Percut Sei Tuan District, Deli Serdang Regency. The population of this study were all mothers who breastfed babies aged <6 months, using a total sampling technique. Hypothesis testing in this research uses a different test (Independent Sample T-Test). The research results found that peer counseling using the health belief model approach was effective in increasing maternal knowledge, attitudes about the success of exclusive breastfeeding (p-value 0.00) and the achievement of exclusive breastfeeding.